Analisis Keamanan Jarak Antar Alat Penyambung Geser (Shear Connector) Berdasarkan Distribusi Tegangan Dengan Menggunakan Metode Elemen Hingga - Dista, Aditia Reshi; Suyadi, Suyadi; Helmi, Masdar (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
The function of the shear connector is to keep concrete plate oriental position. The installation of the shear connector will influence the distribution of the stress spread in unevenly on concrete plate. This research aims to analyse the safe distance of shear connector based on distribution of stress in concrete plate.  This research used software SAP2000 version 14 to find maximum stress on beam then the stress in the plate was analysed by finite element method and Microsoft Excel used base on Kirchoff-Love theories. The analysis result show that maximum stress was located in the middle of span near the support (shear connector). If position of the shear connector not accord with SNI-1729-2015, the plate can crack due to the exceed of modulus concrete crack (fr). The risk of failure increased as line with the wider shear connector distance due to overpass of crack stress.Keywords : Stress, shear connector, plate, finite elemen method, SAP2000.